Legal security in electronic commerce contracts - Madaoui Nadjia (Revista Processus de Políticas Públicas e Desenvolvimento Social, 2024)
The advent of the digital age has transformed the way businesses operate and consumers shop. Electronic commerce (e-commerce) has revolutionized the global marketplace, providing convenience, accessibility, and efficiency. However, this digital revolution has brought about a multitude of legal considerations that must be addressed to ensure legal security in e-commerce contracts. In this article, we delve into the critical aspects that businesses and consumers alike should be aware of to navigate the complex landscape of electronic commerce contracts.